INNOVATIVE METHODS TO IMPROVE THE QUALITY OF INTERNAL AUDIT SERVICES IN THE REPUBLIC OF UZBEKISTAN - Rakhmatullaeva Nargiza Nuriddinovna (Journal Park Publishing, 2022)
The article discusses the main criteria for assessing the effectiveness and quality of the activities of internal audit services. The effectiveness of the internal audit function depends on compliance with generally accepted standards of activity, as well as compliance with regulatory requirements. Each organization independently determines the list of parameters that characterize the effectiveness of the service, developing procedures for calculating and evaluating key indicators in order to obtain an objective assessment.
Keywords: audit, quality, evaluation criteria, position on service, standards, evaluation levels.